Comparison techniques utilized in spatial 3D and 4D data visualizations: A survey and future directions. (October 2017) - Kim, Kyungyoon; Carlis, John V.; Keefe, Daniel F.
Highlights: An exhaustive survey of 3D/4D comparative visualization is done. A taxonomy of 3D/4D comparative visualization techniques is proposed. Four fundamental approaches were identified in literature with discussion of most interesting extensions. The number of data instances supported in the visualizations is small. Hybrid designs and visualization in VR are promising next steps for research. Graphical abstract: Abstract: A variety of visualization techniques can be utilized to compare multiple Spatial 3D or time-varying Spatial 3D data instances (e.g., comparing pre- versus post-treatment volumetric medical images). However, despite the fact that comparative visualization is frequently needed – scientists, engineers, and even humanists must routinely compare such data – visualization users and practitioners suffer from a lack of adequate Spatial 3D comparative visualization tools and guidelines. Here we survey the field and present a taxonomy for classifying existing and new comparison visualization techniques for such data into four fundamental approaches: Juxtaposition, Superimposition, Interchangeable, and Explicit Encoding. The results clarify the key design decisions and tradeoffs that designers must make to create an effective comparative Spatial 3D data visualization and suggest the potential of emerging hybrid approaches, ones creatively combining aspects of the four fundamental approaches.